Development and validation of a RP-HPLC method for quality control of oxantel pamoate, pyrantel pamoat and praziquantel in tablets - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
In the present study, simple, rapid and precise HPLC methods were developed which would be useful for quality control of pharmaceutical dosage forms containing praziquantel (PRZ), pyrantel pamoate (PPA) and oxantel pamoate (OPA). The first method (M-1) was developed for the analysis of PRZ; separation was achieved using a reversed-phase column (4.6 x 150 mm, 5 mu m) C18, a mobile phase comprising ACN:MeOH:20 mM phosphate buffer (0.2 % TEA, pH 4.5) (50: 10: 40, v/v/v) and UV detection at 210 nm. PPA and OPA were analysed simultaneously using a separate method (M-2) by employing the same column and flow rate. In accordance with the second method (M-2), detection wavelength was set at 295 nm and a mobile phase of ACN: MeOH: 20 mM phosphate buffer (0.2 % TEA, pH 4.5) (12: 3: 85, v/v/v) was used. Benazepril hydrochloride (BZP) and paracetamol (PAR) were used as internal standards (IS) of the methods M-1 and M-2, respectively. Both methods were validated based on the parameters such as specifity, linearity, precision, accuracy, limit of detection (LOD) and limit of quantitation (LOQ) besides system suitability tests. Forced degradation studies were performed to indicate specifity of the proposed methods. The methods were found linear over the concentration ranges of 0.5-7.5 mu g/mL, 1-15 mu g/mL and 2-40 mu g/mL for PRZ, PPA and OPA, respectively. Correlation coefficients (r) of the regression equations were greater than 0.999 in all cases. The precision of the methods was demonstrated using intra-and inter-day assay RSD values which were less than 1% in all instances. Accuracy of the proposed methods was tested on placebo tablets spiked with known amounts of actives. Resulting recoveries of assays were in the range of 99.9-101.1 % whereas, those from commercial tablets were 99.4-100.8 %.
Keywords: Oxantel pamoate; Pyrantel pamoate; Praziquantel; HPLC; analytical method validation; PERFORMANCE LIQUID-CHROMATOGRAPHY; MASS-SPECTROMETRY; CAPILLARY-ELECTROPHORESIS; PLASMA; FENBENDAZOLE; SPECTROSCOPY; ALBENDAZOLE; METABOLITES; MEBENDAZOLE; TARTRATE